The (mis)interpretation of the Bible in South Africa: Towards a better hermeneutic - Bradley M. Trout (In die Skriflig, 2021)
The Bible continues to have a prominent place in the South African discourse. Unfortunately, however, it is often poorly interpreted. The purpose of this study was to examine the nature of the misinterpretation of the Bible. We aimed to uncover the specific interpretive methods responsible for this misinterpretation, considered generally in the South African milieu. Specifically, we discussed the role of biblical fundamentalism. Essentially fundamentalism fails to account for the reader’s place in the process of biblical interpretation and so operates under the guise of false objectivity. We then discussed three examples of this phenomenon: the way in which Scripture has been interpreted by the African Christian Democratic Party, Peter Hammond’s view in his Biblical principles for Africa, and the scriptural interpretation of Deuteronomy by Dutch Reformed theologians in the 1930s–1960s. This essay demonstrated that the primary problem with the fundamentalistic method is its failure to account for the reader’s role in the interpretive process. Fundamentalism presents itself in several ways as ‘biblical’ without recognising the problems inherent in such a formulation, especially in the assumption of objectivity. This result illustrated the necessity for a more reader-centred approach to Scripture that takes note of prior ideological commitments. As a result, it is imperative that we embrace a hermeneutic that is firstly ‘critical’, that means willing to interrogate ideological pre-commitments. Secondly, we proposed that the hermeneutic focus on ‘eschatology’, whereby Scripture is considered primarily based on its redemptive trajectory. The emphasis is then placed on the Christ event, especially the resurrection as the culmination of the story. Biblical ethics are then grounded in an understanding of the people of God as the eschatological community. This approach is also termed ‘redemptive-historical’. As one example of such an approach, we discussed N.T. Wright’s Five-act model. In this view, biblical ethics are grounded upon knowing where we find ourselves in the overall drama and what is appropriate within each act. God’s people are to imagine themselves as players in a later stage of the same grand drama of Scripture. This hermeneutic provides, so we argued, a better approach to applying Scripture in the modern context. If we wish to reduce the misinterpretation of Scripture in the South African milieu, we need to identify fundamentalist hermeneutics and continually strive towards a more reader-centred and eschatological approach to its interpretation.